Epigastric and umbilical hernia; work relatedness and return to work. - Ramin Mehrdad; Khosro Sadeghniiat Haghighi; Amir Hossein Naseri Esfahani (Tehran University of Medical Sciences, 2013)
Abdominal wall hernia is common but reliable scientific data about its work relatedness is very limited and inconsistent. In this paper, a less common type of abdominal wall hernia in a 30 year old male worker is presented with recurrence after first surgery when he returned to work. In contrast with almost all kinds of hernia, a lifelong limitation for heavy lifting was recommended. It seems that contrary to popular belief, work relatedness of abdominal wall hernia is seriously doubtful, although conclusive evidences are not enough. It is preferable to make decisions cautiously for return to heavy duties of work after surgery of large umbilical, umbilical & epigastric or incisional hernia, while avoiding recommendations for long days off work after surgery of any hernia.